Efektivitas Program Membangun Keluarga Utama sebagai Program Pemberdayaan Masyarakat Islami (Studi Kasus di KSPPS BMT Tumang) - Al Hadi, M. Qoshid (Jurnal Studi Agama dan Masyarakat, 2019)
Poverty alleviation is a development general agenda all over the world, including Indonesia. Quality and sustainable development is the development capabling of empowering people to alleviate poverty and improve quality of life. The Program of Main Family Building